Ultimate Strength of the Buoy Structure due to the Loads Arise from the Tanker and Mooring Lines - Murdjito Murdjito; Handayanu Handayanu; Resy Agatya (International Journal of Offshore and Coastal Engineering, 2017)
A study was conducted to evaluate the ultimate strength of a 40 ton buoy induced by the dynamic loads arising from a 120,000 DWT Aframax tanker and mooring lines. The buoy is operated at Bangka Strait offshore oil terminal. The evaluation was commenced by analyzing the motion characteristics of the buoy and tanker due to environmental excitations, both in free floating conditions. This is continued by the simulation and time-domain analysis of connected buoy and tanker to observe the hawsers and mooring line tension intensities. The corresponding results show the largest tension occurs in the in-line configuration with the tanker in ballast condition, where hawsers tension reaches 1282.58 kN with a safety factor of 2.23 and mooring line tension 1974.18 kN with a safety factor of 3.20. The resulting tensions were further applied as input data for structural modeling using FEM to find out the stresses develop on the buoy structure. Results of this modeling reveal the maximum value of stress experienced by the buoy structure is approaching 184.28 MPa, which is below allowable stress of 200 MPa. Following this, the ultimate stress of 450 MPa will be violated by 143% incremental load above the maximum, namely 3,116.67 kN and 4,797.26 kN due to the hawsers and mooring line. This fact suggests that the structure is unlikely to experience ultimate failure if merely operated in the current operational site.